2001
DOI: 10.1007/s004120100167
|View full text |Cite
|
Sign up to set email alerts
|

The actin loci in the genus Drosophila : establishment of chromosomal homologies among five palearctic species of the Drosophila obscura group by in situ hybridization

Abstract: Chromosomal homologies among the four palearctic Drosophila obscura group species D. ambigua, D. tristis, D. obscura, and D. subsilvestris and the "trans-palearctic" species D. bifasciata were established by in situ hybridization using the 5C actin gene of D. melanogaster as a probe. In all species two labeling sites were detected in each of chromosomal elements C and E and one in each of chromosomal elements A and D. In addition one labeling site was detected on element B for the species D. subsilvestris and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In the genomes of D. melanogaster (Fyrberg et al 1980;Tobin et al 1980), D. virilis, D. robusta, D. hydei and D. grimshawi (Loukas and Kafatos 1986), D. subobscura and D. madeirensis (Loukas and Kafatos 1988), D. ambigua, D. tristis and D. obscura (Bondinas et al 2001), six actin loci could be observed similarly dispersed over the chromosomal elements A (one locus), C (two loci), D (one locus) and E (two loci). Recently, an additional actin locus on element B was found for D. subsilvestris and D. bifasciata by Bondinas et al (2001).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In the genomes of D. melanogaster (Fyrberg et al 1980;Tobin et al 1980), D. virilis, D. robusta, D. hydei and D. grimshawi (Loukas and Kafatos 1986), D. subobscura and D. madeirensis (Loukas and Kafatos 1988), D. ambigua, D. tristis and D. obscura (Bondinas et al 2001), six actin loci could be observed similarly dispersed over the chromosomal elements A (one locus), C (two loci), D (one locus) and E (two loci). Recently, an additional actin locus on element B was found for D. subsilvestris and D. bifasciata by Bondinas et al (2001).…”
Section: Discussionmentioning
confidence: 92%
“…Recently, an additional actin locus on element B was found for D. subsilvestris and D. bifasciata by Bondinas et al (2001). In D. pseudoobscura and D. persimilis of the pseudoobscura subgroup, the 5C actin probe labeled the six actin sites so far observed in the entire genus Drosophila, but in addition one site in element A and one in element B.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Muller (1940) proposed that the chromosome arms are conserved as homologous elements across the genus Drosophila. This hypothesis has been amply confirmed by, for example, in situ hybridization to polytene chromosomes (see Bondinas et al 2001 and references therein). Cuenca et al (1998) have shown that the F elements of D. melanogaster and D. subobscura are homologous.…”
Section: Introductionmentioning
confidence: 82%